Explorando nexos entre a construção social da criança e as práticas de saúde - Sanine, Patricia Rodrigues [UNESP]; Castanheira, Elen Rose Lodeiro [UNESP] (FapUNIFESP (SciELO), 2018)
This article seeks to correlate the different social meanings attributed to children with health actions directed toward this group starting in nineteenth-century Brazil. The study reviews the literature based on the social concept of “being a child” and its correlation with policies and practices in public health and child care, focusing on actions undertaken within the framework of primary health care. Three different conceptions of the meaning of “child” were identified. The interrelations between transformations in the social construction of the notion of child were investigated, along with the different political and technological proposals involving children in Brazil, indicating the contemporary challenge of developing care technologies that will strengthen children with regard to rights.
Exploring connections between the social construction of the child and health practices
Keywords: Child care; Child health; History of public health; History of the child